Social Security Scheme (letter) - Beveridge, William Henry Beveridge, Baron, 1879-1963
1942 1942 1940s 2 pages 2. As the employers will not pay the 3/3d from their salaries or their profits, and Sir William says it will go on to the cost of production, the consumer will pay, and in the case of the export trade, a tariff on imports will make the consumer pay again. On Sir William's own admission he has only rumbled or shaken up the income available to the British people (the Wages Fund), and suggested - admitted that the British people could spend it more economically to their own advantage. Or is Sir William making provision from the same fund for two or three trade cycles, a world economic blitz, and a third World War? This is not a National Mutual Aid Scheme, as Sir William admits that the employers put their part into the cost of production, and cheerily says, "I have not touched the wealthier classes for the income." The proposals are in the main excellent (except Old Age Pensions) and necessary, but Sir William's three fundamentals are unstable. Mrs. Beatrice Webb has Sir William taped off exactly in "Reynolds News." As an old age pensioner, Sir William, you leave me cold, depressed, and disappointed in my appreciation of you. Sir John Orr computes that for food alone we require ten shillings per week each. You say that you are neither half-way to Moscow, Berlin or Australia. No, but you are like the Good Old Duke of York - when he was only half-way up he was neither up nor down. Yours sincerely, A Trades Unionist & Old-age Pensioner My press quotations are taken from "The Glasgow Herald" of 2nd. December, 1942. QUOTATION MARKS " " 292/150.5/5/236